Stability of talus component in total ankle arthroplasty - Abdul Kadir, Mohammed Rafiq (Springer Berlin Heidelberg, 2008)
Early design of total ankle arthroplasty showed poor clinical outcomes and has since been regarded as an inferior procedure to arthrodesis. Initial attempt of ankle replacement used the design concept for total hip arthroplasty, with the stem implanted into the tibia and the cup implanted into the talus. The procedure was abandoned due to unsatisfactory early outcomes. However, the procedure is gaining popularity lately due to various clinical complications associated with bone fusion. New implants for TAR were introduced with designs that are more closely resembled the natural anatomy of the ankle. Biomechanical analysis of the replaced joint is crucial to achieve better understanding of its behaviour under physiological loading. At present, biomechanics research of the ankle joint after arthroplasty is fairly limited. In this study, finite element analysis was used to examine the stability of two design features of the talus component for total ankle replacement — the single-fin and the double-fin. Three dimensional model of the talus bone was reconstructed from CT dataset and the implant was positioned on the trochlea. The bone was assigned with cortical bone properties and pressure was applied on the superior surface of the implant. Nonlinear contact analysis was performed together with an in-house experimentally validated micromotion algorithm to predict the stability of the implants. Results showed that the talus component with double-fin was more stable than the one designed with single-fin. However, the magnitude of micromotion for both designs did not exceed the threshold limit for osseointegration, suggesting the adequacy of single-fin to provide primary stability.